The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1130/ges02044.1
|View full text |Cite
|
Sign up to set email alerts
|

Early Paleozoic post-breakup magmatism along the Cordilleran margin of western North America: New zircon U-Pb age and whole-rock Nd- and Hf-isotope and lithogeochemical results from the Kechika group, Yukon, Canada

Abstract: Post-breakup magmatic rocks are recognized features of modern and ancient passive margin successions around the globe, but their timing and significance to non-plume-related rift evolution is generally uncertain. Along the Cordilleran margin of western North America, several competing rift models have been proposed to explain the origins of post-breakup igneous rocks that crop out from Yukon to Nevada. New zircon U-Pb age and whole-rock geochemical studies were conducted on the lower Paleozoic Kechika group, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 183 publications
0
12
0
Order By: Relevance
“…In their study focused on rift-related Neoproterozoic and Cambrian rocks exposed in northern Utah and southeastern Idaho, Yonkee et al (2014) advocated for a shift from pure-shear extension during early rifting followed by a second stage of depth-dependent extension. Recent work on similar rocks along the western Laurentian margin (e.g., Beranek, 2017;Campbell et al, 2019;Moynihan et al, 2019) has also suggested a broad analog of Rodinian rifting to better-constrained models of rifting described for opening of the Atlantic Ocean. However, an incomplete and fragmented geologic record of these events along the projected continuation Plot is based on the cross-correlation metric; the axes are arbitrarily calculated values to illustrate similarity of each data set in 2-D space (Saylor & Sundell, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study focused on rift-related Neoproterozoic and Cambrian rocks exposed in northern Utah and southeastern Idaho, Yonkee et al (2014) advocated for a shift from pure-shear extension during early rifting followed by a second stage of depth-dependent extension. Recent work on similar rocks along the western Laurentian margin (e.g., Beranek, 2017;Campbell et al, 2019;Moynihan et al, 2019) has also suggested a broad analog of Rodinian rifting to better-constrained models of rifting described for opening of the Atlantic Ocean. However, an incomplete and fragmented geologic record of these events along the projected continuation Plot is based on the cross-correlation metric; the axes are arbitrarily calculated values to illustrate similarity of each data set in 2-D space (Saylor & Sundell, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Following Beranek (2017) and Campbell et al (2019), we suggest that the second phase of predominantly Ediacaran and early Cambrian rifting (~600-520 Ma), volcanism, and transition to drift along the Cordilleran margin (Yonkee et al, 2014) consisted of depth-dependent and asymmetric crustal thinning during formation of the necking domain ( Figure 14d) and eventual lithospheric breakup (Figure 14e). During this interval, we identified significant stratigraphic differences from the newly documented sections in central Idaho and those of southeastern Idaho, including likely discontinuous sedimentation and less subsidence, as well as exhumation in east central Idaho.…”
Section: 1029/2020tc006145mentioning
confidence: 95%
See 1 more Smart Citation
“…It is possible that CO 2 was sourced by: (i) degassing during volcanism related to the Terreneuvian to Series 2 Cambrian rifting; or (ii) metamorphism of deeply buried carbonate and clastic strata due to high geothermal gradient. Several studies have reported the presence of mafic and tholeiitic volcanism during the same period as rifting in Western Canada (Stewart, ; Cecile et al ., ; Beranek, ; Campbell et al ., ) and it is possible that CO 2 generated during volcanism could have reacted with the deep‐seated serpentinite to liberate large amount of magnesium. Sandiford et al .…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Neoproterozoic and early Paleozoic alkalic plutonic suites in northcentral Idaho have been dated at 665-650 Ma (Lund et al, 2010) and 500-485 Ma (Evans and Zartman, 1988;Lund et al, 2010), and similar age igneous rocks are present along most of the western miogeocline boundary (Lund et al, 2010). Recent investigation of mafic rocks in the southern Yukon Territory yielded zircon ages of 488-473 Ma (Campbell et al, 2019).…”
Section: Neoproterozoic-early Paleozoic Cordilleran Marginmentioning
confidence: 99%